Pantun Dalam Kehidupan Melayu (Pendekatan historis dan antropologis) - Tuti Andriani (Lembaga penelitian dan pengabdian kepada Masyarakat, 2012)
Poem is a poem in Malay literature of the most widely known. In the past rhymes are used to supplement the daily conversation. Even now the majority of Malays in the rural communities still use it. The word connotes a poem, like, like, for instance, or the like. For example, we often hear the words